Studies on Schismatoglottideae (Araceae) of Borneo LIV : A summary of the species of the Schismatoglottis Multiflora Group - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2016)
A taxonomic synopsis, and identification key to species, of the Schismatoglottis Multiflora Group is provided. Schismatoglottis bulbifera H. Okada, H. Tsukaya & Y. Mori is resurrected from S. multiflora Ridl., to which it was relegated, taking the Multiflora Group to 18 species. All species are illustrated from living plants.